2018
DOI: 10.1002/jcp.26961
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA‐9 reduces inflammatory response and fibroblast proliferation in mice with idiopathic pulmonary fibrosis through the ANO1‐mediated TGF‐β–Smad3 pathway

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive interstitial lung disease with increasing occurrence, high death rates and unfavorable treatment regimens. In the current study, we identified the expression of microRNA-9 (miR-9) and anoctamin-1 (ANO1) in IPF mouse models induced by bleomycin, and their effects on inflammation and fibroblast proliferation through the transforming growth factor-β (TGF-β)-Smad3 pathway. To verify the targeting relationship between miR-9 and ANO1, we used bioinformatics predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…is involved in the pathogenesis of IPF [30,31], and increased expression of IGFBP5 and ITGB1 plays a vital role in the development of IPF [32,33]. Our present results suggested that up-regulated hsa_circ_0004099 might promote the development of IPF by decreasing the expression of miR-4633 or miR-9, and further increasing the expression of IGFBP5 or ITGB1, respectively.…”
Section: Discussionmentioning
confidence: 60%
“…is involved in the pathogenesis of IPF [30,31], and increased expression of IGFBP5 and ITGB1 plays a vital role in the development of IPF [32,33]. Our present results suggested that up-regulated hsa_circ_0004099 might promote the development of IPF by decreasing the expression of miR-4633 or miR-9, and further increasing the expression of IGFBP5 or ITGB1, respectively.…”
Section: Discussionmentioning
confidence: 60%
“…Additionally, miR-101 attenuates IPF by inhibiting SMAD3, thus reducing transforming growth factor (TGF)-β expression and inhibiting fibroblast proliferation and activation ( 8 ). Other previous studies have shown that the downregulation of miR-9 targets anoctamin-1, which results in decreased expression levels of TGF-β and SMAD3, slowed progression of IPF and reduced fibroblast proliferation in bleomycin-induced mice ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 83%
“…Recent evidence also implicates this molecule in chemokine signaling (41). In particular, anoctamin-1 has been shown to suppress the release of proinflammatory cytokines, thus hindering the innate immune response (66,67). Accordingly, preliminary data suggest that ANO1 silencing in GIST cells alters the expression of genes involved in immune-related pathways.…”
Section: Discussionmentioning
confidence: 99%